Multinational Corporations vs. Domestic Corporations: International Environmental Factors and Determinants of Capital Structure - Lee, Kwang Chul; Kwok, Chuck C. Y. (Journal of International Business Studies, 1988)
This paper examines whether or not U.S.-based multinational corporations (MNCs) have different capital structures than U.S. domestic corporations (DCs), and if so, what causes the differences. In explaining the difference between the capital structures of MNCs and DCs, previous studies tended to directly discuss the relationships between international environmental factors (e.g., political risk, foreign exchange risk) and the capital structure. A framework of analysis is proposed in this paper that examines the influence of environmental factors on the firm-related capital structure determinants (e.g., agency costs, bankruptcy costs) that in turn affect the capital structure of the MNC. Among the determinants that are examined, more emphasis is placed on the discussion of agency costs since no previous studies have applied this concept in the international arena. Empirical tests were conducted to investigate whether MNCs are significantly different from DCs regarding agency costs of debt, bankruptcy costs, and capital structure. Contrary to conventional wisdom, the empirical findings show that MNCs do not have lower bankruptcy costs and that they tend to have lower debt ratios than DCs.